RETRACTED: Substantiation of the range of changes in the elastic-damping and inertial characteristics of the oscillatory system of agricultural MES with mounted technological equipment - Godzhaev Zakhid; Senkevich Sergey; Uyutov Sergey; Kuzmin Victor; Malakhov Ivan (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001